Prospective NATO or EU membership and institutional change in transition countries - Ansgar Belke; Ingo G. Bordon; Inna Melnykovska; Rainer Schweickert (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper quantifies the impact of incentives related to potential membership on institutional change as measured by the World Bank Governance Indicators (WBGI). Based on a panel of 25 transition countries for the period from 1996 to 2008 we show that pre-accession incentives provided by EU and NATO clearly matter for institutional development. In addition, path-dependency determined by cultural norms may be overcome by economic liberalization while foreign aid seems to hamper institutional development.
Keywords: F15; F20; F50; P20; P30; O19; 330; EU; NATO; transition economies; institutional change; governance; EU-Erweiterung; Bündnissystem; Mitgliedschaft; Übergangswirtschaft; Institutioneller Wandel; Governance-Ansatz; Transformationsstaaten